The Development Of Mathematics Module Based On Relational Thingking - ika santia (Pancaran Pendidikan, 2017)
Mathematical thinking and problem-solving are the important goals of learning mathematics. But in fact, mathematics learning school was focused to compute the final answer. For example in solving algebraic equations, students have difficulty to solvingthese problems because students do not understand about symbols of equivalencies. It shows that student needs a media that stimulates their relational thinking. Therefore, this research aims to develop mathematics module for secondary students based on relational thinking to increase ability in solving an algebraic equation. This is a development research which refersto 3D model. The technique for data collection was taken from questionnaire and test. The results showed that the modul included: validity of the contents 84.21%, validity for language 84.21% and validity of display 86.84%. The results of limite test to thirty students received a positive response 94.73% and score of relational included in good catego